EFEKTIFITAS MEDIASI DI LUAR PENGADILAN DALAM PENYELESAIAN SENGEKETA - Siti Nur Umariyah Febriyanti; Widya Kusuma Ningasih (Smart Law Journal, 2023)
Mediation is an alternative dispute resolution that can be chosen by both parties by involving a mediator as a neutral third party to assist in resolving disputes. The purpose of this research was to determine the effectiveness of out of court mediation in resolving medical disputes. This study uses a normative juridical method with analytical descriptive characteristics and uses qualitative data. Mediation is the most appropriate alternative to dispute resolution in civil cases because mediation process outside the court benefits both parties according to the agreement and runs peacefully.